2022
DOI: 10.26504/rs137
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Primary Care Systems of Ireland and Northern Ireland

Abstract: The mission of the Economic and Social Research Institute is to advance evidencebased policymaking that supports economic sustainability and social progress in Ireland. ESRI researchers apply the highest standards of academic excellence to challenges facing policymakers, focusing on 12 areas of critical importance to 21 st century Ireland.The Institute was founded in 1960 by a group of senior civil servants led by Dr T. K. Whitaker, who identified the need for independent and in-depth research analysis to prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Poorer health levels among older age groups will also have consequences for the potential care burden of the working-age population. The age profile in the two jurisdictions is broadly similar, though there is a slightly higher proportion aged over 65 in Northern Ireland (Connolly et al, 2022). Existing research points to lower life expectancy and a higher prevalence of chronic health conditions (such as heart attack, diabetes, etc.)…”
Section: The Demographic Profilementioning
confidence: 98%
See 1 more Smart Citation
“…Poorer health levels among older age groups will also have consequences for the potential care burden of the working-age population. The age profile in the two jurisdictions is broadly similar, though there is a slightly higher proportion aged over 65 in Northern Ireland (Connolly et al, 2022). Existing research points to lower life expectancy and a higher prevalence of chronic health conditions (such as heart attack, diabetes, etc.)…”
Section: The Demographic Profilementioning
confidence: 98%
“…Existing research points to lower life expectancy and a higher prevalence of chronic health conditions (such as heart attack, diabetes, etc.) in Northern Ireland than in Ireland (see Connolly et al, 2022). These patterns might be expected to have consequences for levels of economic (in)activity in the two…”
Section: The Demographic Profilementioning
confidence: 98%
“…Recent analysis by Brick and Connolly (2021) showed that a significant proportion of people waited more than 12 months for treatment in 2018, with Ireland performing poorly relative to other European countries. The COVID-19 pandemic and the associated restrictions on non-COVID-related hospital activity in 2020 and 2021 have led to a further deterioration in waiting times during 2021 with more than 40% of those on the outpatient waiting list waiting more than one year (Connolly et al, 2022). In addition, shorter waiting times for hospital-based services for those with PHI relative to those without PHI (Whyte et al, 2020) give rise to equity concerns that access to hospital-based services is based on ability to pay rather than need.…”
Section: Hospital Carementioning
confidence: 99%
“…The paralysis of the Stormont institutions has led some young people to feel they are unable to address pressing needs in their lives (such as the cost-of-living or poor mental health) (Shared Island Unit, 2022;Pivotal, 2023). Northern Ireland has also seen the emergence of a healthcare crisis, with already high hospital waiting times climbing rapidly since the pandemic (Connolly et al, 2022).…”
Section: Northern Ireland Political and Social Dynamicsmentioning
confidence: 99%